Preferential school subsidy law and the use of educational improvement plans by teachers and principals. Case: municipal schools in Iquique, Tarapacá region, Chile. - Leiva Martínez, Carlos Eduardo (2022)
In order to determine the relationship between knowledge of the Preferential School Subsidy Law and the use of educational improvement plans by teachers and principals of municipal schools in Iquique, Chile. For this purpose, we used a descriptive-correlational research, with a non-experimental, cross-sectional design. In the educational institutions approached, on the one hand, a sample of 92 teachers was chosen from a universe of 120; and, on the other hand, the entire population of (05) principals was selected, who were surveyed through a questionnaire of forty items, with mixed scaling and pre-coded by levels; the aforementioned instrument was validated and had a very high reliability, Cronbach's Alpha 0.907. The results show that there is a high positive correlation (Rho= 0.815) between knowledge of the Preferential School Subsidy Law (SEP) and the use of educational improvement plans (PME). In addition, high levels of knowledge of the SEP law and use of the PME were identified. Similarly, knowledge of the SEP law shows a high and positive correlation with pedagogical practices (Rho= 0.847), as well as a moderate and positive correlation with accompaniment actions (Rho= 0.558). It is concluded that the high levels of knowledge shown of the law, the high level of use of the plans and the relationship shown between the variables and their indicators reveal great opportunities to develop to the maximum the capacities of those involved in the educational process in the municipal schools studied.